PERAN UNITED NATIONS CHILDREN'S FUND DALAM MENGATASI MASALAH PENDIDIKAN ANAK DI KABUPATEN BOGOR SELAMA PANDEMI COVID -19 PERIODE 2020-2021 - Nabila Syamlan (2023)
The government decided to change the face-to-face learning system to online learning in order to break the chain of disease transmission due to the COVID-19 pandemic. This policy has various impacts, especially for those who do not have educational technology devices. In overcoming problems that arise related to children's education, UNICEF as an international organization is here to help. This study aims to look at UNICEF's role in addressing children's education problems in Bogor Regency during the COVID-19 pandemic for the 2020-2021 period. This research uses interview and document study methods. The theory used in this study is the theory of the role of international organizations and the theory of international cooperation. The results of this study are that UNICEF has played its role as an independent actor and international cooperation has been successful, although the output is not the same between the two parties.